Animal Husbandry: Bestiality in Medieval Culture - Stuhmiller, Jacqueline A. (Explorations in Medieval Culture, 2025)
Introduction: the Stallion and the Unicorn, or, Animal Lovers   Jacqueline A. Stuhmiller Part 1: Bestiality in Theory 1 Contra naturam: Bestiality in Medieval Scientific Discourse   Marian E. Polhill 2 "Between the Paws of a Tender Wolf": Medieval Influences and Other Tales (Un)Told in Angela Carter's The Bloody Chamber   Bailey Flannery Part 2: Bestiality in Practice 3 The Animality of Man: Sexual Transgression and Animal Transformation in a Middle Welsh Prose Tale   Katherine Leach 4 Bestiality, Confession and Social Control in Late Medieval England   Tess Wingard 5 Bestial Intercourse in Cheuelere Assigne   Crystal Beamer Part 3: Marrying the Beast 6 Sympathizing with the Werewolf's Wife: the Dynamics of Trust, Betrayal, and Bestiality in Bisclavret   Larissa Tracy 7 "Wulf, min wulf": Animal Others and Animal Lovers in "Wulf and Eadwacer"   Andrea Schutz Part 4: The Pleasures of Bestiality 8 Bestiality in Medieval Art: Cross-cultural Reflections on a Lascivious Lacuna   Anna Russakoff 9 "Shame to Him Who Thinks Evil": the Deviant Pleasures of Sir Gawain and the Green Knight   Jacqueline A. Stuhmiller Conclusion: Bestiality: Some Things Stay the Same. ...   Joyce E. Salisbury Bibliography 267 Index 275